Analisis Pengaruh PAD, DAU Dan DAK Terhadap Alokasi Belanja Modal Dengan Pertumbuhan Ekonomi Sebagai Variabel Moderasi Pada Pemerintah Daerah Kabupaten/Kota Di Provinsi Jawa Tengah - Hidayati, Nurin, Drs. Atwal Arifin, M.Si, Ak (2016)
The implementation of regional autonomy is to create independence in improving welfare and public services. One local government efforts to improve the welfare of local communities is to provide capital expenditure is higher for development of sectors which are useful in their respective regions. The purpose of this study was to analyze the effect of revenue (PAD), General Allocation Fund (DAU) and Special Allocation Fund (DAK) in Capex, as well as the effect of PAD, DAU and DAK with moderating economic growth in Capex in the District / city of Central Java province. This study used a population of 35 District and City of Central Java from year 2012 to 2014 with a purposive sampling techniques appropriate predefined criteria. The number of samples collected as many as 105. The collected data were analyzed using data analysis conducted prior classic assumption test before hypothesis test. Testing the hypothesis in this study using analytical techniques Moderated Regression Analysis (MRA) with f test, R2 test and t test. These results indicate that the PAD and Economic Growth no significant effect on Capital Expenditure, DAU significant effect on Capital Expenditure by the intensity and the opposite direction, DAK positive and significant impact on Capital Expenditure. Moderating variables (economic growth) able to moderate variable DAU and DAK able to moderate variable intensity and opposite direction but is not able to moderate PAD variables on capital expenditure. Keywords: PAD, General Allocation Fund, Special Allocation Fund, Economic Growth, Capital Expenditure.